Peningkatan Vocabulary Siswa SMK Muhammadiyah 2 Kota Tegal Menggunakan Materi Health And Safety At Work (K3) - Syaefani Arif Romadhon; Iin Indrayanti; M. Taufik Qurohman (Jurnal Surya Masyarakat, 2025)
The need to improve the understanding of students  of  Mechanical Enginnering regarding the concepts of Occupational Safety and Health (OSH) in English is important, considering that this material has only been provided in Indonesian. The lack of mastery of English vocabulary related to OSH poses a serious challenge for students in preparing themselves to compete in the job market, which increasingly demands foreign language skills. Students receive explanations related to OSH in English, vocabulary drilling, pretest, and post-test. The average pretest score obtained by students is 49.2, indicating that the initial understanding level of students is still low. However, after the treatment, the average post-test score increased significantly to 76.1. This increase in average score indicates an improvement in students' understanding of OSH vocabulary material in English.